Assessing the cyclone early warning services of women, children and person with disability: a case study in Nijhumdwip - Shahjahan, Md. (BRAC Univeristy, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2018.